Meningitis Retention Syndrome in an 11-Year-Old Boy: A Case Report of an Underreported Clinical Scenario in Children - Qader, Md Abdul; Begum, Lutfunnahar; Salwa, Zeena (Journal of Pediatric Nephrology, 2019)
Meningitis retention syndrome (MRS) is an underreported clinical syndrome in children that presents with meningitis and acute retention of urine. It is usually associated with aseptic meningitis, but there are case reports of MRS associated with viral and other kind of meningitis. There is no imaging abnormalities in the brain and spine associated with acute urinary retention. Here we report a case of an 11-year-old boy who presented with signs of meningism and acute urinary retention. Further evaluation revealed features of meningitis in cerebrospinal fluid analysis and normal imaging of the brain and spine. He completely recovered from urinary retention after meningitis treatment. Keywords: Meningitis; Urinary Retention; Child; Case Report